PENGARUH DISARTRIA TERHADAP PELAFALAN DIALEK NGAPAK: STUDI KASUS ANAK USIA SEKOLAH DASAR - Annisa Chantika Aulia Wardani; Rizka Prajaning Arum (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2025)
Dysarthria is a complex speech motor disorder in children that affects articulation, with significant implications for children's communication. This study aims to analyze the influence of dysarthria on the pronunciation of Ngapak dialect in elementary school-aged children, focusing on the linguistic transformations produced by neurological disorders. The research method uses a qualitative case study approach, with the subject of a 12-year-old child who has dysarthria, using data collection techniques through voice note recordings on the WhatsApp application. The analysis was carried out by transcribing and identifying the pronunciation patterns of the Ngapak dialect that were modified due to the disorder. The results of this study show that dysarthria produces significant changes in pronunciation, including consonant deletion, nasal sound ambiguity, and articulation modification, especially in the consonants “ng”, “r”, and “l”. The findings reveal that the disorder does not simply impede communication, but actively reshapes the architecture of language. The study concluded that dysarthria has a fundamental impact on language production, with important implications for speech therapy and psychlinguistic understanding. Research recommendations include a holistic approach to intervention, which respects individualized linguistic variation and neurological adaptive capacity.